SIGNIFIKANSI INSTAGRAM SEBAGAI MEDIA PROMOSI BRAND RUANG GURU - Lambok Graceanne (2022)
These days, the use of social media as a medium to carry out promotional activities is a phenomenon that is currently thriving in the midst of society. Through social media, people can share many things with anyone, anytime, and anywhere. Using social media, we can share information using voice or text messages, and we can share it in the form of photos, videos,or audio. Instagram is one type of social media site that has been used by many people, especially in the community of teenagers and adults. Through Instagram, people can provide or get information in the form of photos, videos, audio, and text (captions). One company that uses social media as a medium to carry out promotional activities is PT. Ruang Raya Indonesia, or Ruang Guru, which has an Instagram social media account @ruangguru. Ruang Guru already has more than one million followers on their Instagram account and often uploads various content about company information, services, and promotional content. Cognitive responsetheory will be used as a guide in this research. This study will examine the significance of using Instagram as a promotional medium by Ruang Guru by distributing a questionnaire containing several statements related to this research to a number of samples from Ruang Guru's Instagram account followers. The results obtained from this study indicate that the use of social media, specifically Instagram, plays a significant role as a promotional medium for the Ruang Guru brand. Keywords: Instagram, Social Media, Promotion, Ruang Guru, Significance